Health and Economic Outcomes in the Alumni of the Wounded Warrior Project - Krull, Heather; Oguz, Mustafa (RAND Corporation, 2023)
The Wounded Warrior Project has developed programs to help care for injured service members and veterans. This report describes how project alumnus respondents are faring in domains related to mental health and resiliency, physical health, and employment and finances.